2023
DOI: 10.2147/jpr.s436434
|View full text |Cite
|
Sign up to set email alerts
|

Research Trends of Acupuncture Therapy for Chronic Pain-Related Depression or Anxiety from 2003 to 2023: A Bibliometric Analysis

Pu Yang,
Tian Wang,
Yu-Jun He
et al.

Abstract: Background Chronic pain (CP) as a long-lasting stressor can often cause mood disorders, such as depression or anxiety. The comorbidity of CP and mood disorders poses challenges for treatment and increases healthcare costs. Acupuncture has emerged as a widely utilized approach to alleviate both CP and mood disorders. However, there is a lack of well-established bibliometric analyses in this area of research. Therefore, this study aimed to identify the current hotspots and research trends regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…It was observed that the authors have fixed partners and lack cooperation with other team authors ( 75 , 76 ). If authors from different research directions break through the constraints of profession, discipline, team, institution, and region, research on CHs will achieve greater progression ( 77 , 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the authors have fixed partners and lack cooperation with other team authors ( 75 , 76 ). If authors from different research directions break through the constraints of profession, discipline, team, institution, and region, research on CHs will achieve greater progression ( 77 , 78 ).…”
Section: Discussionmentioning
confidence: 99%